Japan as a market and source of supply - Allen, G.C. (Oxford : Pergamon Press, 1967)
The book begins with an outline of Japan's recent economic development and a description of the outstanding features of her economy. The description of the changing structure of the export and import trades and of Japan's relations with her various trading partners is supported by a number of statistical tables
Includes bibliographical references and index
osc 28/01/2019
Loans
Keywords: Commerce; Economic history; Japan